Remittance behaviour of intra-EU migrants: Evidence from Hungary - László Kajdi; Anna Sára Ligeti (Comparative Population Studies (CPoS), 2020)
After the eastern expansion of the European Union (EU), a large number of emigrants left their home countries to work in economically better developed western member states. Hungary followed this EU emigration trend with a certain time lag. However, the rising number of emigrants caused structural problems in the domestic labour market. A comprehensive examination of intra-EU remittances as one of the major determinants of migration has been outside the scope of recent research activity. The data from the Hungarian Microcensus survey and the first Hungarian household survey focusing on the topic of remittances can provide a valuable case study of intra-EU private transfer flows. The aims of this study are twofold. On the one hand we intend to provide empirical evidence for the major factors that determine remittance propensity by calculating probit regressions. On the other hand, OLS regressions are calculated in order to introduce variables which are associated with money transfers. These results are interpreted within the theoretical framework of the New Economics of Labour Migration (NELM) to identify the underlying motivations for remittances. The most important findings are that older men with vocational school education have the highest remittance propensity, and the likelihood of sending private support is higher among short-term migrants. As the key factors, the income of the sender person is positively associated with the sum of money flows, while the income of the receiving household is negatively associated. Within the theoretical framework of NELM, these results favour the dominance of altruistic motives, since supporting the household members who remain behind seems to be the major driving force. However, when intentions of returning home are considered in the models, it seems that self-interest might also play a role as a driver of remittances. Within this study, the main focus was on the characteristics of the senders, meaning that a possible field of future research could be an examination of these questions from the perspective of remittance receiver households.
urn:nbn:de:bib-cpos-2020-04en1
Keywords: 300; Labour-market; Remittances; European Union; Migration policy